Construction of an M2 macrophage-related prognostic model in hepatocellular carcinoma - Song, Huangqin; Wang, Xiaoxiao; Zhang, Chao; He, Jiefeng (Frontiers in Oncology, 2023)
Background: M2 macrophages play a crucial role in promoting tumor angiogenesis and proliferation, as well as contributing to chemotherapy resistance and metastasis. However, the specific role of M2 macrophages in HCC tumor progression and their impact on clinical prognosis remain to be further elucidated. Materials and methods: macrophage M2-related genes were screened using CIBERSORT and WGCNA analysis, and subtype identification was performed using unsupervised clustering. Prognostic models were constructed using univariate analysis/LASSO Cox regression. Additionally, GO/KEGG, GSEA, GSVA, and mutation analysis were used for further analysis. The relationship between Riskscore and tumor mutation burden (TMB), microsatellite instability (MSI), the efficacy of TACE, immunotype, and molecule subtypes were also investigated. Moreover, the potential role of Riskscore was explored using ESTIMATE, TIDE algorithms, and stemness index such as mRNAsi and mDNAsi. Additionally, R package “pRRophetic” was used to examined the correlation between Riskscore and chemotherapeutic response. Finally, we investigated the role of the TMCC1 in hepG2 cells using various techniques, including western blotting, RT-PCR, transwell assays, and wound healing test. Results: This study identified 158 macrophage M2-related genes enriched in small molecule catabolic processes and fatty acid metabolic processes in HCC. Two macrophage M2-related subtypes and a 4-gene prognostic model was developed, revealing a positive correlation between the Riskscore and advanced stage/grade. The high-risk group exhibited higher proliferation and invasion capacity, microsatellite instability, and the degree of stemness. Riskscore was identified as a promising prognostic marker for TACE response, and the high-risk subgroup showed higher sensitivity to chemotherapeutic drugs (sorafenib, doxorubicin, cisplatin, and mitomycin) and ICI treatments. The expression levels of four genes related to macrophage-related Riskscore were investigated, with SLC2A2/ECM2 showing low expression and SLC16A11 /TMCC1 exhibiting high expression in HCC. In vitro experiments showed that TMCC1 may enhance the migration ability of HepG2 cells by activating the Wnt signaling pathway. Conclusion: We identified 158 HCC-related M2 macrophage genes and constructed a macrophage M2-related prognostic model. Our study advances the understanding of the role of M2 macrophages in HCC and proposes new prognostic markers and therapeutic targets.